ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP PADA SOAL SPLDV - Hikmah, Ainul; Roza, Yenita; Maimunah, Maimunah (Media Pendidikan Matematika, 2019)
Students' communication skills need to be described because they are used as communication tools in solving problems given. This study aims to find out and analyze students' mathematical communication skills and their obstacles to the topic of two-variable linear equation systems. This type of research is descriptive research. The research subjects consisted of 6 students divided in high, medium and low-ability students who were selected from 20 students, class VIII students of Riau Global IT Middle School Pekanbaru in 2018/2019. The method used is tests and interviews. The results obtained by the overall achievement were 70% of the achievement of indicators expressing mathematical ideas by speaking, writing, showing, and describing them visually, 66.7% for indicators of understanding, interpreting, and evaluating mathematical ideas presented in the form written, oral, or visual and 40% for the achievement of indicators using vocabulary, notation, and mathematical structures to represent ideas, describe relationships, and model situations. Whereas the obstacles to mathematical communication skills found are the ability of prerequisites that are not fulfilled, low reading and writing skills and low mathematical understanding of students.